The central role of god in the Islamic worldview - Abdul Razak, Mohd Abbas; Hassan Mydin, Shaik Abdullah (CENTRIS, IIUM, 2025)
In a world dominated by countless ideas and ideologies, and the compartmentalization of people in their ways of thinking, this humble article aims to explore the topic of the Islamic worldview. Central to the discussion of the Islamic worldview is the position occupied by God as the Creator of the entire universe. Given the topic's vastness and space limitations, the writers have chosen to focus solely on the central position occupied by God.